The Role Fasting In Metabolism And Tumor Progressive - Abdullah Waheed, Zainab; Habeeb Sarhan , Nadia; Mohammed Shaker, Mustafa; Mahmood Kadhim AL-Zubaidy, Israa; Ghaleb Idreess, Hawraa (Medical Science Journal for Advance Research, 2022)
Background: Fasting is the voluntary abstinence from food and drink for a fixed period of time while remaining faithful to certain rules. Fasting has been practiced by humans since ancient time. Fasting involved in the regulation of many metabolic processes correlated with transitioning into a process capable of Energy production and carbon-based metabolism mainly from Tissue adipose and muscular parts. The differences in the levels in the blood hormones and metabolites help to lower and eventually defend normal cells from chemical insults in the cell division and metabolic activityFasting Can induce an anti-warburg response by reducing glucose absorption Carriers (GLUTs) and aerobic glycolysis and force cancer cells to Improve in oxidative phosphorylation (OxPhos); It improves efficiency in cancer cells and, subsequently, toxic products of reactive oxygen (ROS). DNA, p53, DNA damage , and death of the cells , particularly Chemotherapy response,Fasting serves as improving anti-tumour immunity By Fasting or FMD. Conclusion Fasting regulates many physiological functions associated with transitioning into a process capable of producing energy and carbon-based metabolic activity mainly from adipose and muscular tissue., The fasting action is largely dictated by the levels of glucose, glucagon, insulin, GH, IGF1, and adrenaline in the blood.,Some many discrepancy in the rates at which hormones and metabolites circulate are normally found during fasting, allowing antitumor response . ,fasting reaction Protects significant nerves and glia but still doesn't prevent glioma or neuroblastoma, Cyclophosphamide, and pro-oxidant Compounds, and preserves the embryonic mouse Doxorubicide fibroblasts.